Risk Mitigation of Emerging Zoonoses: Hendra Virus and Non‐Vaccinating Horse Owners. Issue 6 (4th January 2017) - Manyweathers, J.; Field, H.; Jordan, D.; Longnecker, N.; Agho, K.; Smith, C.; Taylor, M.
Summary: Hendra virus was identified in horses and humans in 1994, in Queensland, Australia. Flying foxes are the natural host. Horses are thought to acquire infection by direct or indirect contact with infected flying fox urine. Humans are infected from close contact with infected horses. To reduce risk of infection in horses and humans, Australian horse owners are encouraged to vaccinate horses against the virus and adopt property risk mitigation practices that focus on reducing flying fox horse contact and contamination of horses' environment with flying fox bodily fluids. This study investigates uptake of four Hendra virus risk mitigation practices in a sample of non‐ and partially vaccinating horse owners living close to previous Hendra virus cases. Protection motivation theory was used to develop a conceptual model to investigate risk perception and coping factors associated with uptake of risk mitigation practices. An online survey was administered via Facebook pages of veterinary clinics close to previous Hendra virus cases. Factors associated with uptake of risk mitigation practices were investigated using univariate and multivariate binary logistic regression. Belief that a risk mitigation practice would be effective in reducing Hendra virus risk was significantly associated with the uptake of that practice. Issues around the practicality of implementing risk mitigation practices were found to be the greatest barrier to uptake. Factors that relate to risk immediacy, such as nearby infection, were identified as more likely to trigger uptake of risk mitigation practices. The role of veterinarians in supporting Hendra risk mitigation was identified as more influential than that of respected others or friends. Findings from this study are being used to assist stakeholders in Australia responsible for promotion of risk mitigation practice in identifying additional pathways and reliable influencing factors that could be utilized for engaging and communicating with horse owners to promote Hendra virus risk mitigation behaviour.